The Effect of Hydraulic Coupling on Mechanical Deformation Characteristics of Shallow Coal Seam in Western Mining Area. (12th March 2022) - Ling, Chunwei; Shi, Xiaoshan; Wang, Hao; Zhang, Kangning; Ren, Qingshan; Lv, Yinghua
Abstract : During coal mining, the mechanical and deformation behavior of the overburden is affected by water and stress. Therefore, it is of great significance to study the mechanical behavior of the surrounding rock under the action of hydraulic coupling. For high-intensity mining with shallow coal seam and large mining and strong strata behavior in stope, the hydraulic support is often damaged. Based on basic experiments and physical similarity simulations, overburden fracture in shallow coal seam in western mining area under hydraulic coupling was studied. The results show that under the loading rate range of 0.5 5 mm/min, the compressive strength of sandstone increases with the loading rate. The faster the loading rate, the shorter the duration of the rock sample being loaded and damaged, and the fewer the acoustic emission events. The first weighting step of the main roof of the working face is 54 m, the periodic weighting step is 12.75 28 m, and the average periodic weighting step is 22 m. There are only caving zone and fractured zone in the overburden of working face; the height of caving zone and fractured zone is 60 m and 168 m, respectively. The strength of the saturated sample is significantly reduced. During the excavation of the working face, the temperature difference between the fracture and the overburden value is ≥1°C, which can be used as a threshold for judging the development range of overburden fracture in similar simulation experiments.